THE ROLE DIGITAL COMPETENCE ON LECTURER PERFORMANCE OF S1 ACCOUNTANCY STUDY PROGRAM OF PRIVATE UNIVERSITIES IN BANDUNG METROPOLITAN AREA THROUGH WORK SATISFACTION WITH SERVANT LEADERSHIP AS MODERATING VARIABLE - Kusdanu Waskito, Saptono (Dinasti Publisher, 2021)
The purpose of this research is to prove that there is an effect of digital competence on the performance of lecturers in the S1 Accounting Study Program in Private Universities in Bandung Metropolitan Area through job satisfaction with Servant Leadership as a Moderating variable. The population is 478 lecturers. The number of samples was 218 lecturer respondents. The sample was determined based on the proportionate stratified simple random sampling method, meaning that all lecturers were given the same opportunity to become respondents regardless of the position strata held by the S1 Accounting Study Program of Private Universities in Bandung Metropolitan Area. The data was declared valid, reliable and The research results prove that there is an effect of digital competence on the performance of lecturers in the S1 Accounting Study Program in Private Universities in Bandung Metropolitan Area through job satisfaction with Servant Leadership as a moderating variable. Improvement must start from digital competence because it contributes to the smallest influence.